Sistem Ekonomi Islam Sebagai Solusi Problematika Sistem Kapitalisme Dan Sistem Sosialisme - M. Indra Gunawan (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2020)
In this study, the title published by the author is the Islamic economic system as a solution to the problems of the capitalism system and the socialism system. This research has a broad scope both in terms of theory and application, for that purpose the objective is to find out the problems of the economic system of Capitalism and the economic system of socialism in overcoming economic problems and to see what is offered by the Islamic economic system in overcoming the problems of the economic system of capitalism and the economic system. economics of socialism, the research methodology used is library research or